ANDRÉS BELLO AND THE CHILEAN CIVIL CODE: CORNERSTONES OF THE PRIVATE LAW SYSTEM OF LATIN AMERICA - Filip Olszówka (Zeszyty Prawnicze)
This article describes the international inﬂuence of the 1855 Civil Code of the Republic of Chile, presenting the geographical extent of its impact, the reasons for its popularity, and the ways in which it was received. The basic idea behind this Code was its Pan-American approach, which was a key feature of the worldview espoused by its Venezuelan maker Andrés Bello, who compiled the Code for the Republic of Chile. To compose his Code and create the foundations of an integrated Pan-American identity, Bello combined the features shared by all the ex-Spanish colonies in South America, that is the Castilian culture and legal tradition, with the revolutionary inspiration of the independence movement of his times. Most of the countries in the region adopted Bello’s Code, either in part or in its entirety, and many are still using its legacy today. Moreover, the inﬂuence of Bello’s Civil Code transcended the borders of the South American continent, reaching other former Iberian colonies and even as far afield as Japan.